Corporate Social Responsibility (CSR) Disclosure on Politically Connected-Family Firms - Iman Harymawan; Mohammad Nasih; Diarany Sucahyati (Journal of Accounting and Investment, 2022)
Research aims: This study examines the relationship between political connections and family ownership toward CSR activities disclosure.Design/Methodology/Approach: This study employed 624 Indonesian public companies on the Global Reporting Initiative (GRI) list for 2010-2018. The researchers used OLS (Ordinary Least Squares) regression by considering the fixed effect diversity of industry, year, and type of GRI to examine the relationship between political connections and family ownership on CSR disclosure.Research Findings: This study discovered that companies with political connections disclosed more CSR activities because they desired to bind themselves with the government, instruments of legacy, and social motivation. However, family firms were not found to have a significant relationship with CSR disclosure. In addition, the strong family ownership in the firm impacted the reduced strength of political connections, thereby reducing the company's CSR activities disclosure. Theoretical contribution/Originality: This study is interesting because the researchers combined the issue of the politically connected board and family firms, which are frequently found in the context of Indonesian companies. The researchers expect this study to enhance corporate board characteristics and CSR disclosure literature. Practically, the researchers expect this study could provide useful information for investors to make investment decisions. Furthermore, this study provides insight for regulators, who need a view of how political connections and family companies exist in responding to the regulations they set. Therefore, the existing regulations can be improved. Yet, this study was limited to the proxy of political connection based on local regulation of politically exposed person (PEP).